Roles of Leader, Internal Factors and Human Resource Policies and being a Healthy Organization: A Case Study of DHL (Thailand) in Eastern Seaboard Industrial Estate - ติรธรรมเจริญ, ปิติ (Thai Interdisciplinary and Sustainability Review, 2019)
The study of roles of leadership internal factors and human resource policies in that impact on Healthy Organization of DHL (Thailand) has 1) to study the relationship between roles of leadership and being a healthy organization of DHL (Thailand) 2) to study the relationship between the organization factor and being a healthy organization of DHL (Thailand) and 3) to study the relationship of human resource management policy and being a healthy organization of the DHL (Thailand). The findings showed that human resource management. Policy in total and in each dimension was at a moderate level. Organizational factors in total and in each dimension were at moderate level, the leadership in total and in each dimension were at moderate level. a healthy organization in total and in each dimension were at moderate level. These factors affect the of human resources management policy for health as well as the organization's adaptability. Organizational factors affecting the organization as a whole and the health and Factors affecting the level of leadership to the organization as a whole and healthy aspect. A member of people for sample group were 400 that is base on Krejcie & Morgan table on confident level 95 percent. The research used questionnaire at the research tool. The analysis was based on mean, standard deviation and Multiple Regression.